ORANG TUA FIGUR IDOLA ANAK : KONSEP PENDIDIKAN POLA ASUH ISLAM - Zuyyinah Candar Kirana (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Parents play a role and are responsible for their children, so they are not badly affected by the increasingly rapid advances in digital technology. Parents must also play a role as teachers, friends, and idols for children. When children feel that their parents are idols, children will always rely on their parents, be obedient and follow what their parents say and do. If parents are kind to their children, children will surely idolize their parents. If parents have become idols, teaching kindness to children will be very easy. Parents are every child's first teacher. Therefore, parents play a very important role in shaping the mental and character of children. By implementing Islamic education parenting in educating children, of course children will grow up to be good, pious, independent, tough and not easily swayed by technological developments and times. Children will have a strong stand and be ready to face the challenges of the times. Certainty in the strength of faith, the power of knowledge and adab possessed will be a provision when children find problems with the twists and turns of life.